Modelling the factors that Influence the awareness on ADHD of children among primary school teachers: a PLS – SEM approach / Mohd Noor Azam Nafi ... [et al.] - Nafi, Mohd Noor Azam; Zu, Shahida; Hasan, Nur Afifah; Tuan Mohd Ariffin, Nik Izati Bayani; Mohd Shafie, Siti Nurhafizah; Ab. Aziz, Nasuhar (Unit Penerbitan UiTM Kelantan, 2021)
Attention Deficit Hyperactive Disorder (ADHD) is among the most discovered psychological problems among children in Malaysia. Children with ADHD will face problems with their academic performance since they lack focus and attention in class. This study aimed to investigate the factors influence the awareness of ADHD among children among primary school teachers using PLS-SEM approach. Primary data was used by the researchers as the source of data for this study by distributing the questionnaires. SmartPLS was used to define the effects between the variables. Based on the output, the relationship between awareness and perception has a moderate positive linear relationship while knowledge and attitude have a weak positive relationship towards awareness. The result also shows that knowledge and attitude have significant influences towards awareness. Hence, teachers should gain more knowledge about ADHD. Besides, teachers should have a positive attitude towards the students that have discipline problems because they may suffer from ADHD.